THE RELATIONSHIP OF PERCEIVED PARENTING STYLES AND EMOTIONAL INTELLIGENCE OF GENERATION Z AMONG SELECTED SCHOOLS IN CEBU CITY - Antone L. Abellanosa, Ma. Mia Monica H. Chavez, Gieannil R. Nacario, Karla Mae E. Rivera, Ronald C. Yrog-Irog, (Chelonian Research Foundation, 2024)
Abstract - The way parents interact with their children can have a big impact on how their emotional intelligence develops. The purpose of this study is to identify emotional intelligence and which parenting styles are most perceived among Cebu City's Generation Z, as well as the relationship between those parenting styles and emotional intelligence. This study utilized a quantitative approach with a descriptive correlational research design using standardized tests such as the Perceived Parenting Style Scale and the Emotional Intelligence Self-Assessment Tool. The researchers collected data from 385 respondents who were 18– 25 years old and lived in Cebu City. The result revealed that the most perceived parenting style of Generation Z among selected schools in Cebu City is authoritative parenting, and the respondents have a high level of emotional intelligence. Moreover, the results also showed that the respondents have high levels of emotional intelligence in all of its domains. However, the result also found that there is no significant correlation between the three perceived parenting styles when compared individually to the domains of emotional intelligence.